2020
DOI: 10.5603/arm.a2020.0176
|View full text |Cite
|
Sign up to set email alerts
|

Validity of ROX Index in Prediction of Risk of Intubation in Patients with COVID-19 Pneumonia

Abstract: Introduction: One important concern during the management of COVID-19 pneumonia patients with acute hypoxemic respiratory failure is early anticipation of the need for intubation. ROX is an index that can help in identification of patients with low and those with high risk of intubation. So, this study was planned to validate the diagnostic accuracy of the ROX index for prediction of COVID-19 pneumonia outcome (the need for intubation) and, in addition, to underline the significant association of the ROX index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 7 publications
(10 reference statements)
5
42
0
3
Order By: Relevance
“…The cut-off value used in the included studies varied from 2.7 to 5.9 in obtaining the homogenous and clinically acceptable cut-off value. We excluded the extreme outlier cut-off value of 25.26 in the paper published by Suliman et al [ 21 ]. Based on the studies included in the meta-analysis, the optimal cut-off value may fall close to 5 of ROX index within the 24 h of admission for predicting HNFC failure.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off value used in the included studies varied from 2.7 to 5.9 in obtaining the homogenous and clinically acceptable cut-off value. We excluded the extreme outlier cut-off value of 25.26 in the paper published by Suliman et al [ 21 ]. Based on the studies included in the meta-analysis, the optimal cut-off value may fall close to 5 of ROX index within the 24 h of admission for predicting HNFC failure.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ROX index cut-off points to predict success of HFNC therapy in COVID-19, different studies reported similar points to those proposed by Roca et al 27 and Hu et al11, with a population similar to ours in terms of demographics and comorbidities, concluded that 6 hours after HFNC onset with a cut-off point at 5.55 was the most suitable predictor of HFNC success, albeit with a relatively low sensitivity (61.1%) and relatively high specificity (84.6%); in contrast, in the present study the best predictor of HFNC success is the ROX index 24h after therapy onset, with a cut-off point of 5.35, which yielded better results in sensitivity, specificity, PPV, NPV and AUC than those proposed by other studies.10, 11, 13, 28 Recently have been published prospective studies evaluating utility of ROX index in COVID. 29 , 30 , 31 Mellado-Artigas et al, 29 in a multicenter prospective study that included 259 patients with severe pneumonia due to SARS-CoV-2 who reveived HFNC at ICU admission, found that baseline non-respiratory Sequential Organ Failure Assessment (SOFA) score and ROX index were associated with endotracheal intubation and mechanical ventilation. Suliman et al, 30 in a prospective study that included 69 patients with moderate and severe COVID found that ROX index measured on the first day of admission was independent predictor factor of intubation with a cut-off point <25.26; a very high cut-off point is striking in this study, 30 fact for which it was not included in a recent meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, recent data indicated that the ROX index had moderate utility in predicting IMV in patients infected with COVID-19, especially in cases with moderate to acute respiratory failure [30]. Suliman et al [12] showed that AUC value, as a predictor of IMV, on the first day of admission in non-ICU-conditions was 0.897; however, this was in a small study of 69 patients with pneumonia, so studies with larger sample sizes and patients with varying degrees of severity will be necessary to support these results. On the other hand, prepandemic studies showed that, in acute hypoxemic respiratory failure [31], the value of the SpO2/FiO2 ratio serves as control during noninvasive mechanical ventilation [32], or as a proxy measure for the calculation of the sepsis-related organ failure assessment score when partial pressure of oxygen in arterial blood is not available [33]; however, evidence related to COVID-19 is more limited.…”
Section: Discussionmentioning
confidence: 99%
“…These observations highlight the need to identify objective measurements of early predictors of mechanical ventilation [10,11]. Under normal conditions, arterial blood gases can determine true oxygenation status but, in the current pandemic situation, non-invasive solutions are needed to guide actions as early as during hospital triage [12,13].…”
Section: Introductionmentioning
confidence: 99%